The Protective Effect of Pilose Antler Peptide on CUMS-Induced Depression Through AMPK/Sirt1/NF-κB/NLRP3-Mediated Pyroptosis - Hu, Yue; Zhao, Min; Zhao, Tong; Qi, Mingming; Yao, Guangda; Dong, Yu (Frontiers in Pharmacology, 2022)
Background: Pilose antler peptide (PAP), prepared from the pilose antler of Cervus Nippon Temminck, is widely used in Traditional Chinese Medicine (TCM) against various inflammatory disorders. TCM prescriptions containing pilose antler are often prescribed clinically to treat depression. However, the pharmacological mechanisms of how PAP against inflammation prevents and treats depression remain poorly understood. Methods: PAP was identified using denovo sequencing and Database searching. Then, behavior tests were conducted to investigate the effect of PAP on CUMS- exposed mice. In parallel, Nissl staining and Golgi-cox staining were used for exploring the effect of PAP on neural cells and dendritic spine density. Additionally, the expression of key proteins of the AMPK/Sirt1/NF-κB/NLRP3 pathway was analyzed by Western blot. Finally, the CUMS procedure was conducted for 6 weeks. At 5th week, PAP and fluoxetine (Flu) were intragestrically treated for 2 weeks. Silencing information regulator related enzyme 1 (Sirt1) inhibitor EX-527 and AMP-activated protein kinase (AMPK) inhibitor Dorsomorphin were employed to investigate the effects of Sirt1 and AMPK on the PAP-mediated depression. Results: PAP attenuated the behavior alteration caused by CUMS stimulation, decreased the number of neurons, and restored the dendritic spine density. PAP treatment effectively up-regulated the expression of p-AMPK, Sirt1, and suppressed the expression of Ac-NF-κB, NLRP3, Ac-Caspase-1, GSDMD-N, Cleaved-IL-1β, and Cleaved-IL-18. Moreover, selectively inhibited Sirt1 and AMPK was able to compromise the therapeutic effect of PAP on depression. Conclusion: The present work indicated that PAP has a protective effect on CUMS-induced depression. In addition, AMPK and Sirt1 played critical roles in the PAP-relieved depression. PAP might be a potential therapeutic option for treating depression.